Neighbours of People Who use Nyaope are Anxious Too! - Ramatsui, Oria; Ngema, Vukile; Mokwena, Kebogile; Maaga, Khomotso; Rhavhengani, Machaka (Nurture, 2025)
Purpose: The purpose of the study was to determine the prevalence and severity of anxiety symptoms among neighbours of people who use nyaope. Nyaope, a very addictive substance with severe consequential social and behavioral impacts, is reported to contribute to mental disorders including anxiety symptoms among family members of users. However, the members of the immediate community are also affected due to various activities associated with nyaope usage. Methodology: A quantitative design was used to collect data from four hundred and twenty-two (422) adult neighbours of people who use nyaope in six townships of Tshwane Municipality in Gauteng, South Africa. The Generalized Anxiety Disorder (GAD-7) questionnaire that was used to screen for anxiety symptoms had the following four categories: no symptoms, mild, moderate and severe symptoms. Findings: The participants were comprised of 48,46% males and 51,54% females and their age ranged from 18 to 88 years. The prevalence of anxiety symptoms was 53.62 % (n=222), with the majority presenting mild symptoms (n=112; 27.05%), followed by moderate (n=78; 18.84%) and severe (n=32; 7.73%). The factors associated with anxiety symptoms were age, gender and religion. Conclusion: Neighbours of people using nyaope have anxiety symptoms that are higher than the general public. The community around nyaope usage is mostly assumed to be disaffected by this, but the study proves otherwise. Practical Implications: Psycho-social support should be provided to community members living in areas of rife nyaope use. Contribution to Literature: This study would contribute important literature on how nyaope usage affects the immediate community.